Audiovisual Media and Its Implications in Art Therapy: A Review of Anti-Bullying Instrumentation (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
The phenomenon of bullying among Indonesian teenagers shows an alarming trend with a significant increase in cases. Art therapy-based intervention approaches through audiovisual media offer the potential for innovative solutions, but valid and reliable measurement instruments are needed to objectively evaluate their effectiveness. This study aims to systematically examine psychometric characteristics and the application of bullying behavior measurement instruments in the context of art therapy-based audiovisual media intervention.. This study uses the method of systematic literature review with content analysis of previous studies. The data source is obtained from published scientific literature in the period 2010-2024 which discusses bullying measurement instruments and art therapy interventions. Studies show that the Likert scale questionnaire is the dominant instrument used, with adaptations of standardized instruments such as the Illinois Bully Scale and Olweus Bully/Victim Questionnaire. The results of the analysis of the instrument showed excellent psychometric characteristics with item validity values ranging from 0.497-0.751 and reliability Cronbach's alpha 0.930. This instrument is able to measure various dimensions of bullying behavior comprehensively covering physical, verbal, social, and cyber aspects. The integration of art therapy interventions through audiovisual media with standardized measurement instruments provides a comprehensive approach to bullying prevention. This study recommends the use of instruments with tested psychometric characteristics to ensure accurate and reliable evaluation of interventions